A resource-efficient mobility management scheme to analyze handoff performance in PNEMO environment - Islam, Shayla; Hassan Abdalla Hashim, Aisha; Hasan, Mohammad Kamrul (IEEE, 2020)
Mobility management is characterized into two sections are mainly location management as well as handoff management. The previous one focuses on location updates though the later one oversees consistent Internet availability while the Mobile Router (MR) diverges its point of attachment during movement to the new network. Subsequently, recurrent movement of the Mobile Routers (MR) becomes one of the noteworthy characteristics in mobile networks. Since, as per the standard Network Mobility Basic Support Protocol (NEMO BSP), the MR uses single interface to connect to the new access network. MR needs altering its point of attachment to the network once it moves to the new access networks. This leads to decrease network performance, scalability issues as well as extra signaling overhead that results in higher handoff delay, packet loss, mobility anchor load and total handoff cost (signaling cost, packet delivery cost and energy consumption cost respectively). Consequently, this paper proposed a resource efficient Mobility Management- scheme to analyze handoff performance in PNEMO (MM-PNEMO). From that point onward, signifies a comparative study among the MMPNEMO, NEMO BSP, and PNEMO.